Tonsillar germinal center reactivity regulation and aging - Puyssegur, Juliana (2021)
While tonsillar hyperplasia is the most frequent cause of tonsillectomy in children younger than 10,abscesses and acute infections are responsible for most tonsillectomies in teenagers. Whereverextracellular ATP (a DAMP) becomes abundant in the body, ectonucleotidases CD39 and CD73 areconsidered vital in the generation of an immunosuppressive microenvironment through adenosineproduction. Our goal was to investigate a potential metabolic adaptation of tonsillar B cells, promotinga suppressive behavior upon years of hyperplasia due to local chronic inflammation. By analyzingtonsillar mononuclear cells (TMC) using FACS, we compared co-expression of the ectonucleotidasesCD73 and CD39 on CD20+ cells at different donor ages. We found that samples from older childrenpresented a statistically significant higher double positive CD73+ CD39+CD20+ cell population thanthose from younger patients (37.7% ± SD 10% vs 25.8% ± SD 8.8% respectively, n=40, p<0.01). Byculturing TMC with IL2/IL4/CpG/CD40L, we also show that activated B cells reliably downregulatedCD73, presumably to prevent autocrine adenosine signaling. Thus, we found that neither IL10+CD20+cells nor IL17+CD20+, generated upon stimulation, expressed CD73. In contrast, changes in CD39expression with B cell activation resulted more variable between patients. Finally, we used thepercentage of germinal center B cells (GC) as a read out of the effector immunological activity of theorgans. We found that the proportion of GC within CD20+ cell population steadily declined withincreasing age. GC B cells represented approximately one third of all the B cells from tonsils within the(2-9) year old range (29% ± SD 14%). That value declined to 15.7% ± SD 9.7% in tonsils from 10 to18. Differences between the means were statistically significant (n=50, p<0.01). We concluded that theprogression on the cause of tonsillar disease with age might illustrate the adaptation of the tonsillartissue to constant inflammation.